Comprehensive Project Risk Management Methodology - Copertari, Luis F. (Advances in Social Sciences Research Journal, 2021)
The objective of this paper is to introduce and discuss the basics of a methodology called the Probabilistic Critical Path Method (PCPM) for managing the previously identified risks (uncertainty) of the three project management dimensions: time, cost and return (performance). An interactive Graphic User Interface (GUI) has been designed for visualizing the tradeoffs among these three dimensions as well as their uncertainties on a flat computer screen. The user can choose to visualize the probability of failure (exceeding some user given due date, budget or not exceeding a given Minimally Attractive Rate of Return – MARR) or the probability of success (not exceeding the due date and the budget and exceeding the MARR). PCPM allows for comprehensive project risk management and it constitutes a new integrative project risk management framework. This paper shows that it is possible to integrate all three project management dimensions (time, cost and return) and show their known risks as well as determining the optimal cost and the associated time and return for such optimal cost. Finally, it is possible to interactively show all this multidimensional information on a flat computer screen.